A questionnaire survey on the usage of low protein staple foods by people with phenylketonuria in Scotland. Issue 6 (6th January 2014) - Cochrane, B.; Schwahn, B.; Galloway, P.; Robinson, P.; Gerasimidis, K.
Abstract Background There is scarce evidence available with respect to an evaluation of the role of low protein staple foods (LPSF) in the management of phenylketonuria (PKU). The present study explored beliefs, acceptability and issues around the use of LPSF by people with PKU or their carers. Methods A semi‐anonymous questionnaire was posted to 178 people with PKU in Scotland (104 children, aged 2–17 years, and 74 adults). Questions explored were: the type and amount of LPSF ordered; perceptions on use and usefulness of LPSF; acceptability of the LPSF sensory properties (i.e. taste, smell, texture, appearance); support for the supply and use of LPSF; and comments from primary healthcare professionals regarding dispensing and prescription. Results Eighty‐two individuals responded (46% response rate): 97% perceived that LPSF were useful for PKU management; more than 85% reported that LPSF were important for phenylalanine control, satisfying appetite, and diet variety. The most common LPSF ordered were pasta/rice/cous cous, flour, biscuits and bread. Fifty percent of respondents ordered <51% of the recommended unit allowance of LPSF. The sensory properties of LPSF were well perceived. Forty‐nine percent (n = 39) had received a comment from primary healthcare staff regarding the prescription or dispensing of LPSF; 59% (n = 23) received negative comments, the majority of which came within general practitioner surgeries. Conclusions There is a positive attitude and perception on the use and usefulness of LPSF in the management of PKU. Issues with respect to the supply and provision of LPSF within primary health care may indicate poor communication between specialists and primary healthcare professionals or a lack of scientific evidence demonstrating their clinical effectiveness.